ANALISIS DESAIN PROFIL CAMSHAFT TERHADAP UNJUK KERJA MOTOR C-SERIES 132 CC SOHC - Hendra Khusbianto; Thina Ardliana; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
One way to maximize the engine power of the bore up motor is by modifying the camshaft, so as to get an efficient volumetric. The purpose of this study is to determine the effect of variations in the total duration of the modified camshaft on motor performance. The research method used is the experimental method by varying the modified camshaft with a total duration value of 235°, 236°, and 238° and the standard camshaft with a total duration of 222.5° by testing using a dynotest engine to measure power and torque, burret tube and stopwatch to measure fuel consumption. The results of this study indicate that the modified camshaft with variations in total duration can significantly increase power and torque. The standard camshaft produces a maximum power and torque of 14.27 (HP) and a torque of 12.2 (Nm), while the modified A camshaft produces a maximum power and torque of 16.21 (HP) and a torque of 13.22 (Nm), the modified B camshaft produces a maximum power and torque of 16.84 (HP) and a torque of 13.69 (Nm), and the modified C camshaft produces a power and torque of 16.08 (Hp) and a torque of 13.42 (Nm). In this study it can be concluded that increasing the total duration value can increase power, torque, and fuel consumption.